C9 Different forms of huntingtin in various tissues of transgenic minipig model increase with age. (13th September 2016) - Vidinská, Daniela; Vochozkova, Petra; Ardan, Taras; Juhas, Stefan; Motlik, Jan; Ellederova, Zdenka
Abstract : Background: The progression of Huntington's disease (HD) in human patients is predominantly linked with formation of aggregates, oligomers, and fragments of huntingtin (Htt). Aggregates have been related to cell death, but on the contrary, smaller soluble forms of mHtt and huntingtin oligomers were described to be toxic to the cells and to be the key factors of cellular dysfunction. Therefore we focus on the detection of these forms of Htt in our unique large animal model; transgenic minipig (TgHD) expressing mutant N-terminal (548 aa, 124 CAG/CAA) part of human huntingtin. Aims: To follow disease development in transgenic minipigs by detecting different forms of Htt and comparing them with wild-type (WT) siblings. Methods: We perform immunohistochemical and biochemical methods (Western blots, filter retardation assay, velocity sedimentation, etc.) on different tissues at various ages with main focus on brain in order to detect different forms of Htt. Results: We observed that in cortex of TgHD minipigs, fragmentation increases with age. In addition, we have detected that fragmentation is tissue-specific. For example from all the tissues tested, we are able to see fragments mainly in the cortex, cerebellum, lung and testes of TgHD minipigs, and significantly less in other tissues. Using velocity sedimentation we have identified unphosphorylated mHtt in higher structures in TgHD minipigs. Conclusion: We provide information about HD phenotype development in transgenic minipig model, to be able to test new therapeutic approaches. Acknowledgement: This study was supported by CHDI Foundation (A-5378) and by National Sustainability Programme, project number LO1609 (Czech Ministry of Education, Youth and Sports). The research leading to these results has received funding from the Norwegian Financial Mechanism 2009–2014 and the Ministry of Education, Youth and Sports under Project Contract no. MSMT-28477/2014 (project ID 7F14308).